PENDAMPINGAN PEMETAAN KARANG BENGANG DI DESA TEGALLALANG KABUPATEN GIANYAR - Kardinal, D.A.; Laintarawan, P.; Juliarthana, I.N.H. (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Green open space (RTH) is an absolute necessity in spatial planning. RTH has many functions such as ecologically, socio-culturally and aesthetically. Existing condition up to now shows that the existence of green open space is far from ideal proportions. Previously, Bali has local wisdom for green open space known as karang bengang. Karang bengang is a shared green open space (green belt) that functions as the boundary of traditional villages in Bali. The form is empty land, rice fields, plantation or forests. Its existence is increasingly disappearing due to the need for space and is not protected from modern spatial planning due to the lack of understanding about karang bengang even by the Balinese people themselves. Tegallalang District, based on 2021 data, is the highest sub-district in Gianyar Regency that has experienced conversion of agricultural land. Tourism attractions and accommodation in Gianyar Regency are currently still concentrated in three sub-districts, namely Ubud, Tegallalang, and Payangan (Ulapan). Unfortunately, karang bengang as a local wisdom  has not yet become a landscape system that is integrated with Tegallalang sub-district tourism. This community service provided by Universitas Hindu Indonesia (UNHI) aims to help traditional villages and the government in Tegallalang Village in mapping the karang bengang in Tegallalang Village using ArcGIS so that the results of this map become the basis for carrying out spatial planning that does not sacrifice local wisdom but is expected to have synergy with tourism activities. Keywords: traditional_green open space, karang bengang, mapping, traditional village, tegallalang